Analisis Perubahan Kebijakan Luar Negeri: Kebijakan China terhadap Korea Utara pada Isu Krisis Misil di Semenanjung Korea - Dwita Artsy Fitria; Mohamad Rosyidin (Journal of International Relations Diponegoro, 2021)
This research discusses the changes in China’s foreign policy in the issue of the missile crisis that occurred in the Korean Peninsula. The main actor on the Korean Peninsula crisis is North Korea, which is a traditional ally of China. Hence China holds a crucial position in carrying out its foreign policy on this issue. This research attempts to provide answers regarding the level of the change and the factors driving this policy. This research uses Hermann's concept of foreign policy change. The finding in this research is that change in China’s foreign policy occurs at the program level, where the main goal of China in carrying out its foreign policy in the issue of the Korean Peninsula missile crisis is fixed, but change occurs in the method of policy implementation. In addition, this study also found that the driving factor for the policy came from external pressures therefore it had implications in China's foreign policy towards North Korea.